Predictors of Malignancy and Recommended Follow-Up for Patients with Negative Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Suspected Pancreatic Lesions - Bret J Spier; Eric A Johnson; Deepak V Gopal; Terrence Frick; Michael M Einstein; Siobhan Byrne; Rebecca L Koscik; Jinn-Ing Liou; Terri Broxmeyer; Suzanne M Selvaggi; Patrick R Pfau (Canadian Journal of Gastroenterology)
BACKGROUND: Endoscopic ultrasound (EUS) with fine-needle aspiration (FNA) can characterize and diagnose pancreatic lesions as malignant, but cannot definitively rule out the presence of malignancy. Outcome data regarding the length of follow-up in patients with negative or nondiagnostic EUS-FNA of pancreatic lesions are not well-established.